Unified theory of acceptance and use of technology (UTAUT) model as means to maximise teacher collaboration in the indigenisation of mathematics pedagogy - Bayaga, A.; Madimabe, M. (South African Journal of Higher Education, 2024)
Prior research reveals a persistent lack of interest from teachers to engage in content-based collaborative teaching communities. This obscurity often results in teachers working in isolation, detrimentally affecting the implementation of indigenized innovative digital pedagogies. The current study investigates the interplay between teacher collaboration and the indigenization of secondary school mathematics pedagogy (SS-MP) via the UTAUT model. A cross-sectional study was conducted in South African rural secondary schools, aiming to examine the extent to which teacher collaboration contributes to the indigenization of SS-MP and how this relationship can be measured and assessed within the context of the UTAUT model. Stratified random sampling was used in selecting participants in the survey. Partial least squares structural equation modelling (PLS-SEM) was employed to analyze the measurement and structural models guided by five (5) hypotheses. The sample comprises one-hundred and fourteen educators. The findings revealed significance of behavioural intention (BI) and attitude (ATT) in predicting the successful indigenisation of mathematics teaching practices. User behavior (UB) reveals potential for refinement in predictive performance. Policy implications do emphasise tailoring educational technology integration policies, with reference to infrastructure and supportive conditions. For managerial level, targeted professional development initiatives as well as positive social influences are crucial. The general position though is understanding of technology acceptance in secondary school mathematics, by providing practical guidance responding to culturally settings and technology integration.